2001
DOI: 10.4319/lo.2001.46.8.2080
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of local bed shear stress in streams using a Preston‐static tube

Abstract: Local bed shear stress (Τw) is a fluid dynamic parameter of importance in determining the physical and biological characteristics of stream‐bed environments. Unfortunately, it is often difficult to measure Τw under field conditions. Herein we describe the use of a Preston‐static tube, which is essentially a surface‐mounted Pitot‐static tube, to measure Τw in mountain streams. Our results indicate that it is possible to measure local shear stress quickly, consistently, and inexpensively in the field. This techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…1). In this case, u* was taken as the von Karman's constant ( ϭ 0.4) multiplied by the slope obtained from a graph of velocity (u) versus height (ln z) in the logarithmic region of the boundary layer (Ackerman and Hoover 2001). The velocity profiles were obtained using sil- ver-coated hollow glass spheres (mean diameter 16 m, density 2.0 g cm Ϫ3 , Potters Industries), which were tracked in a particle image velocimetry (PIV) system (Lasiris Magnum SP diode laser, StockerYale; Model 500 Pulse Generator, Berkeley Nucleonics; TM-9701 Progressive Scan Camera, PULNiX America; Video Savant Version 3.0, IO Industries; PIVView 2.1, PivTec GmbH), and measured velocities, based on 150 image pairs, were obtained in 1-mm vertical resolution.…”
Section: Methodsmentioning
confidence: 99%
“…1). In this case, u* was taken as the von Karman's constant ( ϭ 0.4) multiplied by the slope obtained from a graph of velocity (u) versus height (ln z) in the logarithmic region of the boundary layer (Ackerman and Hoover 2001). The velocity profiles were obtained using sil- ver-coated hollow glass spheres (mean diameter 16 m, density 2.0 g cm Ϫ3 , Potters Industries), which were tracked in a particle image velocimetry (PIV) system (Lasiris Magnum SP diode laser, StockerYale; Model 500 Pulse Generator, Berkeley Nucleonics; TM-9701 Progressive Scan Camera, PULNiX America; Video Savant Version 3.0, IO Industries; PIVView 2.1, PivTec GmbH), and measured velocities, based on 150 image pairs, were obtained in 1-mm vertical resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical profiles of the momentum boundary layer at the upstream and downstream locations were obtained for V. spiralis and V. americana in the flat and twisted configurations using PIV. Shear velocities, which were determined by multiplying the von Karman constant (=0.41) by the slope of the velocity vs ln(z) in the logarithmic portion of the boundary layer (Ackerman and Hoover, 2001), were used to estimate k c and the ␦ DSL (Dade, 1993) where:…”
Section: Scmentioning
confidence: 99%
“…Both the Pitot tube and ADV measurements contained uncertainties because of the effects of the angle of attack. Ackerman and Hoover (2001) showed that for a Pitot-static tube oriented at angles up to ±20°, relative to the direction of the approaching flow, the velocity measurements were reasonably consistent. In the Pitot tube tested, the probe support ensured that the angles of attack were below this limit.…”
Section: An Alternative Methods For Measuring Velocities In Open-channmentioning
confidence: 81%